Outcomes of Patients with Portal Vein Thrombosis Undergoing Live Donor Liver Transplantation - Saidi, R. F. (Avicenna Organ Transplantation Institute, 2014)
Background: Live donor liver transplantation (LDLT) for patients with portal vein thrombosis (PVT) creates several technical challenges due to severe pre-operative condition and extensive collaterals. Although deceased donor liver transplantation in patients with PVT is now routinely performed at most centers, the impact of PVT on LDLT outcomes is still controversial. Objective: To determine the outcome of patients with PVT who underwent LDLT. Methods: We reviewed the outcome of adult patients with PVT who underwent LDLT in the USA from 1998 to 2009. Results: 68 (2.9%) of 2402 patients who underwent LDLT had PVT. Comparing patients with and without PVT who underwent LDLT, those with PVT were older (53 vs 50 yrs), more likely to be male, had longer length of stay (25 vs 18 days) and higher retransplantation rate (19% vs 10.7%). The allograft and patient survival was lower in patients with PVT. In Cox regression analysis, PVT was associated with worse allograft survival (HR=1.7, 95% CI: 1.1–2.5, p<0.001) and patient survival (HR=1.6, 95% CI: 1.2–2.4, p<0.001) than patients without PVT. Conclusions: Patients with PVT who underwent LDLT had a worse prognosis than those without PVT.